Association of apolipoprotein B/apolipoprotein A1 ratio and cardiovascular events in rheumatoid arthritis: results of the CARMA study - Zegarra-Mondragón, Sixto; López-González, Ruth; Martín-Martínez, María Auxiliadora; García-Gómez, Carmen; Sánchez-Alonso, Fernando; González-Juanatey, Carlos; Manrique Arija, Sara; Bonilla Hernán, Gema; Martínez Pardo, Silvia; Ruibal Escribano, Ana; Pagán García, Encarnación; Delgado Frías, Esmeralda; et al. (Clinical and experimental rheumatology, 2020)
To assess the plasma apolipoprotein B/apolipoprotein A1 ratio and its potential association with cardiovascular events (CVE) in patients with rheumatoid arthritis (RA).OBJECTIVESTo assess the plasma apolipoprotein B/apolipoprotein A1 ratio and its potential association with cardiovascular events (CVE) in patients with rheumatoid arthritis (RA).A baseline analysis was made of the CARdiovascular in rheuMAtology Project (CARMA), a 10-year prospective study evaluating the presence of at least one CVE in 775 Spanish patients with RA. Of them, 29 had already experienced CVE prior to the inclusion in the study. We assessed the association between the elevation of the apoB/apoA1 ratio with the presence of CVE according to a logistic regression model for possible confounding factors. We also analysed the main parameters of activity of RA and parameters related to lipid metabolism. RA patients were classified according to treatment: patients treated with disease-modifying anti-rheumatic drugs without biologics and those undergoing biologic therapy (anti-TNF-α, anti-IL-6 receptor, and other biologic agents).METHODSA baseline analysis was made of the CARdiovascular in rheuMAtology Project (CARMA), a 10-year prospective study evaluating the presence of at least one CVE in 775 Spanish patients with RA. Of them, 29 had already experienced CVE prior to the inclusion in the study. We assessed the association between the elevation of the apoB/apoA1 ratio with the presence of CVE according to a logistic regression model for possible confounding factors. We also analysed the main parameters of activity of RA and parameters related to lipid metabolism. RA patients were classified according to treatment: patients treated with disease-modifying anti-rheumatic drugs without biologics and those undergoing biologic therapy (anti-TNF-α, anti-IL-6 receptor, and other biologic agents).The apoB/apoA1 ratio of patients who had experienced CVE was higher than that of patients without previous CVE (0.65 vs. 0.60). However, the difference between both subgroups did not reach statistical significance (p=0.197). It was also the case after the multivariate analysis [OR: 1.48 (95% CI: 0.15-14.4); p=0.735]. RA patients from the group with CVE were more commonly receiving lipid-lowering treatment with statins than those without CVE history (41.4% vs. 20%, p=0.005). High HAQ and high atherogenic index were significantly associated with the presence of CVE. There was no statistical association between the type of biologic therapy used in RA and the presence of CVE.RESULTSThe apoB/apoA1 ratio of patients who had experienced CVE was higher than that of patients without previous CVE (0.65 vs. 0.60). However, the difference between both subgroups did not reach statistical significance (p=0.197). It was also the case after the multivariate analysis [OR: 1.48 (95% CI: 0.15-14.4); p=0.735]. RA patients from the group with CVE were more commonly receiving lipid-lowering treatment with statins than those without CVE history (41.4% vs. 20%, p=0.005). High HAQ and high atherogenic index were significantly associated with the presence of CVE. There was no statistical association between the type of biologic therapy used in RA and the presence of CVE.No association between ApoB/apoA1 ratio and CVE was found at the baseline visit of patients with RA from the CARMA study.CONCLUSIONSNo association between ApoB/apoA1 ratio and CVE was found at the baseline visit of patients with RA from the CARMA study.